British Policy-Making and the Need for a Post-Brexit Policy Style - Richardson, Jeremy (Springer International Publishing, 2018)
Jeremy Richardson is Emeritus Fellow at Nuffield College, University of Oxford, UK, and Adjunct Professor at the National Centre for Research on Europe at the University of Canterbury, New Zealand. He is Co-Editor of the Journal of European Public Policy. This book revisits and re-defines the policy style concept and explores the long-standing debate in British political science concerning how best to characterise the British policy style. The book highlights several trends that suggest that the British policy style has shifted towards the impositional end of the policy style spectrum, bringing it more in line with the traditional Westminster model of governing. However, these changes also reflect a more frenetic policy style which might increase the number of policy blunders and failures in British Government unless means are found to access and manage the specialist expertise that interest groups possess.